Elementary preservice teachers’ knowledge, perceptions and attitudes towards fractions: A mixed-analysis - Rosli, Roslinda; Goldsby, Dianne; Onwuegbuzie, Anthony J.; Capraro, Mary Margaret; Capraro, Robert M.; Gonzalez, Elsa Gonzalez Y. (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2020)
Previous research has shown knowledge, perceptions, and attitudes are essential factors during mathematics classroom instruction. The current study examined the effects of a 3-week fraction instructional unit using concrete models, problem-solving, and problem-posing to improve elementary preservice teachers’ knowledge, perceptions and attitudes towards fractions. A quasi-experiment design was implemented to gather data via closed-ended, open-ended, and essay tasks from a convenience sampling of 71 female elementary preservice teachers during pre- and post-assessments. The study discovered that the select preservice teachers were weak in the content knowledge specifically on unit-whole, part-whole, equivalent area, arithmetic operations, and ordering fractional values. In contrast, the incorporation of concrete models, problem-solving and problem- posing was effective in improving the preservice teachers’ level of pedagogical content knowledge, perceptions and attitudes towards fractions. Implications of the results and suggestions are discussed.